2022
DOI: 10.3389/fpubh.2022.864955
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Social Rumor Characteristics During the COVID-19 Pandemic in China

Abstract: BackgroundIn the early stage of the COVID-19 outbreak in China, several social rumors in the form of false news, conspiracy theories, and magical cures had ever been shared and spread among the general public at an alarming rate, causing public panic and increasing the complexity and difficulty of social management. Therefore, this study aims to reveal the characteristics and the driving factors of the social rumors during the COVID-19 pandemic.MethodsBased on a sample of 1,537 rumors collected from Sina Weibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…As unverified information is iteratively presented and propagated, initially dubious rumors may progressively gain credibility during dissemination, leading to an amplification of risks and rendering individuals susceptible to the sway of collective emotions. This phenomenon exacerbates conflicts within the context of public health incidents ( 8 ), with panic-mongering rumors being the most socially damaging ( 9 ). Therefore, the governance of rumors is of great concern in all countries and regions and is an important area of social governance.…”
Section: Introductionmentioning
confidence: 99%
“…As unverified information is iteratively presented and propagated, initially dubious rumors may progressively gain credibility during dissemination, leading to an amplification of risks and rendering individuals susceptible to the sway of collective emotions. This phenomenon exacerbates conflicts within the context of public health incidents ( 8 ), with panic-mongering rumors being the most socially damaging ( 9 ). Therefore, the governance of rumors is of great concern in all countries and regions and is an important area of social governance.…”
Section: Introductionmentioning
confidence: 99%
“…Negative rumors tend to evoke extreme emotions among internet users, while positive rumors embody the public’s optimistic outlook for the future ( 38 ). Negative rumors exhibit a functional characteristic, implying their negative intent, containing imprecise negative information directed toward individuals, society, or the nation ( 39 ). Neutral rumors emphasize adopting a neutral stance toward rumors, aiming to present standardized statements, plain text, and complete characterizations ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…This paper mainly conducts empirical research on the public boycott epidemic prevention and control behaviors under public health emergencies, enriching the research content of previous public risky behaviors. Currently, empirical studies have been conducted on risky behaviors such as panic buying behaviors, 22 illegal and criminal behaviors, [23][24][25] selfdestructive behaviors, and unhealthy behaviors during public health emergencies. 6,7 However, empirical studies on boycott epidemic prevention and control behaviors under public health emergencies are still relatively scarce.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…By further reviewing the literature, firstly, we found that empirical studies on public risky behaviors during public health emergencies mainly focuses on panic buying behaviors (such as masks, alcohol, antiviral drugs, vegetables, and fruits), 22 illegal and criminal behaviors (such as assault, battery, theft, property crime, fraud, drug crimes, extortion, and homicides), 23–25 self-destructive behaviors (such as excessive drinking, self-harm, and commit suicide), 6 , 26 and unhealthy behaviors (such as smoking, sedentary, and a decline in daily physical activity), 7 while empirical studies on boycott epidemic prevention and control behaviors of the public are relatively scarce. 27 Secondly, we found that few studies have explored the effect of psychological distance on public risky behavior under public health emergencies, but most of them have examined the effect of psychological distance on public protection/prevention behavior.…”
Section: Introductionmentioning
confidence: 99%